1965
DOI: 10.1177/004051756503500310
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Linking of Cotton Cellulose by Aliphatic Dicarboxylic Acids

Abstract: Cross-linked, fibrous, cellulose diesters have been prepared using trifluoroacetic anhydride as a condensation agent for reaction of cotton fabric with eleven different, terminally-substituted, dicarboxylic acids ranging from malonic acid (C 3) to eicosane- 1,20-dicarboxylic acid (C22). In the range C2 to C5, only malonic acid reacts readily, oxalic acid being unreactive, while succinic and glutaric acids have qnly slight reactivity. With diadds from C6 to C 22, reaction occurs readily and a decrease in reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, extensive research has attempted to develop nonformaldehyde crosslinking agents to replace N-methylol compounds that release formaldehyde during production and storage, which is suspected of being carcinogenic. Several polycarboxylic acids have been considered as durable press finishing agents for cotton fabrics [1][2]5]. The most effective is 1,2,3,4-butanetettacarboxylic acid (BTCA).…”
mentioning
confidence: 99%
“…However, extensive research has attempted to develop nonformaldehyde crosslinking agents to replace N-methylol compounds that release formaldehyde during production and storage, which is suspected of being carcinogenic. Several polycarboxylic acids have been considered as durable press finishing agents for cotton fabrics [1][2]5]. The most effective is 1,2,3,4-butanetettacarboxylic acid (BTCA).…”
mentioning
confidence: 99%
“…The adipate group was selected versus other possible x-carboxy cellulose esters since it is the shortest chain possible that would provide an unfavorable transition state (7-membered ring in this case) for autocatalysis of the ester linkage, promoting good hydrolytic stability. Synthesis of pure, well-characterized cellulose adipates had to our knowledge been unknown in the literature, prior to our recent work (Kar et al 2011); the only pertinent prior reports dealt with reaction of cellulose fibers and surfaces with adipic acid to cross-link and modify textile properties (Campbell and Francis 1965;Rowland and Brannan 1968). Kar et al reported that a direct approach to the synthesis of cellulose adipate esters, by reaction of cellulose or cellulose esters in solution with adipic anhydride, was plagued by problems of rapid gelation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, the performance of the crosslinked cotton fabrics was not satisfactory because the catalysts used were not efficient enough to ensure effective crosslinking of cellulose. Since the late 1980s, extensive efforts have been made to use polycarboxylic acids as durable press finishing agents for cotton to replace the formaldehyde-based dimethyloldihydroxylethyleneurea (DMDHEU) due to the increasing concern with the toxicity of formaldehyde.…”
Section: Introductionmentioning
confidence: 99%